Photochemical reactivity of ancient marine dissolved organic carbon - Beaupré, Steven R.; Druffel, Ellen R. M. (Geophysical Research Letters, 2012)
Marine dissolved organic carbon (DOC) is the largest reservoir of reduced carbon in seawater and persists up to 4,000-6,000 conventional radiocarbon (C-14) years on average. Photochemical degradation has been suggested as a geochemical sink for these long-lived molecules, yet there have been no studies relating photochemical lability to the C-14-ages of surface DOC. We observed apparent second order (2 degrees) kinetics with respect to DOC and a strong trend from Delta C-14-enriched to depleted values during exhaustive photomineralization of surface marine DOC with high energy UV light. Geochemically, these results suggest that surface DOC is an isotopically-heterogeneous mixture of molecules for which photochemical lability and C-14 ages are correlated. Photochemical mineralization may therefore be an important control on the persistence of C-14-depleted DOC in the ocean. Citation: Beaupre, S. R., and E. R. M. Druffel (2012), Photochemical reactivity of ancient marine dissolved organic carbon, Geophys. Res. Lett., 39, L18602, doi:10.1029/2012GL052974.
id: 2249; PT: J; TC: 0; UT: WOS:000309136800001